Penerapan model pembelajaran realistic mathematics education (rme) untuk meningkatkan transfer of knowledge higher order thinking skills pada materi penyajian data peserta didik kelas v sekolah dasar - Amalia Rizky Purnama; Hartono Hartono; Anesa Surya (Didaktika Dwija Indria, 2019)
This research is a classroom action research with the aim of increasing HOTS in data presentation material by applying the RME learning model. The subjects of this study were 28 fifth grade students at SDN Bayan No. 216 years 2018 / 2019. The research was carried out in two cycles of action. Data collection techniques used tests, observation and documentation with data analysis, source triangulation and content validity. The percentage of HOTS Ability conditions in class V students in classically in pre-action showed 32.24%, the first cycle in the first learning resulted in a percentage of 42.86%, the second learning was 57.14%. The research continued with the second cycle with the percentage of achievement in the first learning amounting to 78.57%, the second learning was 82.14%.